Kálvinizmus és politikai (ön)reprezentáció a kora újkorban: Megjegyzések a magyar patriotizmus eszmetörténetéhez - Tóth, Zsombor (Studia Litteraria, 2012)
This study is an interpretive attempt to propose new arguments regarding the emergence and evolution of early modern Hungarian patriotism. I claim that first the Protestant, and later on the Calvinist martyrologies also undertook the function of advancing various behavior patterns or discourses promoting loyalty towards the “true” church, and this tendency eventually evolved into a notion of patriotism, which was equally connected to the church and the nation. Furthermore, I also argue that the reinterpreted and re-evaluated Protestant culture of martyrology delineated a certain type of narrative, the so called récit martyrologique, which became the new prototype of early modern memoires. These narratives conveyed the written testimonies of their authors’ deeds, and in fact imitated the confessions of saints and martyrs. For a Calvinist, the martyr fulfilled the functions and expectations related to one particular ideal, namely, an elected individual ready to undertake the greatest sacrifice for religion, church and fatherland.Having surveyed the early modern European culture of martyrology and its major texts, my second objective is to reflect on their contemporary Hungarian reception. Relying on three relevant authors like István Nagy Szőnyi, János Komáromi and Miklós Bethlen, I identify the specific Hungarian uses and applications of Calvinist martyrology. In the light of these results I propose the thesis that despite their small number, Hungarian martyrologies had a significant effect on contemporary Calvinist intelligentsia, contributing to the emergence and emulation of loyalty, first towards the Church, then towards the nation and/or the Fatherland. Thus, the cultural origins of nineteenth-century Hungarian national heroes seem to reach back to the early modern martyrs of the seventeenth century.